Vaccination and immunization status among healthcare students: results from the SAVES survey. (30th September 2020) - Rivolta, S; Letzgus, M; De Nard, F; Gaiazzi, M; Principi, N; Margherita, M; Florio, E M; Gervasi, F; Castaldi, S
Abstract: Background: Adequate vaccination coverage among healthcare workers, including students in healthcare professions (SHPs), is crucial in order to prevent spreading of infections within healthcare facilities. However, vaccination coverage among SHPs is often inadequate. We aimed to describe the vaccination/immunization status of SHPs of the University of Milan. Methods: We spread an e-survey to the academic e-mail addresses of postgraduate medical residents and to first- and last-year undergraduate SHPs. The questionnaire covered sociodemographic data (age, sex, education, municipality of residence, internship in high-risk wards) and the reported vaccination/immunization status for Influenza (previous flu season), Varicella, MPR and DTaP vaccines. Results: Among 5743 invited SHPs, 884 participated in the survey. The study sample comprised 462 medical residents and 422 undergraduate SHPs (medicine 176, nursery 186, midwifery 4, healthcare assistance 32, prevention techniques 24). Median age was 27 years (IQR 7); 68.4% participants were female; 91.3% had attended high school in a lyceum, while others in a professional (2.9%) or technical (5.8%) institute; 36.7% lived in municipalities of < 20.000 inhabitants, while 26.1% of > 250.000. Traineeships took place in high-risk wards for 46% of participants. Reported vaccination coverage for Influenza was 33, 7% (with higher coverage for pediatric nursing and midwifery students, medicine students and medical residents). Participants reported immunity (either vaccine or natural immunity) to Varicella in 93, 3% cases. Declared vaccination coverage for Hepatitis B was 94, 1%; 91, 7% participants reportedly completed the MPR schedule, 76, 2% the recommended DTaP booster. Conclusions: Influenza vaccination coverage was suboptimal in our sample of SHPs, suggesting the need of specific educational programs and targeted vaccination campaigns, which may help shaping a positive vaccination attitude for future healthcare professionals. Key messages: Immunization status for VPDs is suboptimal among Italian students in healthcare professions. The monitoring of the immunization status should include healthcare students actively involved in healthcare activities.